The Effectiveness of Using Trello as a Learning Tool for PjBL to Improve Senior High School Students' Hortatory Writing Text - Beta Carella; Arik Susanti (International Journal of Educational Technology and Society, 2025)
This study aims to investigate the effectiveness of using Trello as a learning tool in project-based learning (PjBL) to improve senior high school students' hortatory exposition text writing skills. The research employed a quasi-experimental method with a pretest-posttest control group design. It was conducted in one of the senior high schools located in Sidoarjo, Indonesia. The total population of the study consisted of 202 students, from which a sample of 60 students was selected using purposive sampling. The sample was divided equally into two groups: an experimental group and a control group. The experimental group was taught using Trello as part of the PjBL approach, while the control group received instruction through a conventional learning method. The instruments used to gather data were writing essay tests and a writing assessment rubric. Data were collected through pretests and posttests to assess students' writing performance. The statistical analysis showed that there were significant differences in the writing outcomes between the two groups. The experimental group’s mean pretest score was 64.50, which improved to 91.23 in the posttest. Meanwhile, the control group’s pretest score averaged 64.37 and increased to 83.80 in the posttest. Notably, the improvement in the experimental group was more substantial, particularly in the areas of content development and text organization. These findings indicate that integrating Trello into a project-based learning framework can significantly enhance students’ abilities in writing hortatory exposition texts. In conclusion, the use of Trello as a collaborative digital platform within PjBL has a positive impact on students’ writing skills and can serve as an effective learning tool in EFL writing classrooms.